Unveiling the Association Between Principal Learning-Centered Leadership and Teacher Collaboration: The Mediating Role of Psychological Safety - Savas, Gokhan; Arslan, Kürşat; Kılınç, Ali Çağatay (Routledge Journals, Taylor & Francis Ltd, 2026)
This study develops and tests a theoretical model in which principal learning-centered leadership serves as the independent variable, psychological safety acts as a mediator, and teacher collaboration serves as the outcome variable. Data were gathered from 394 primary and secondary school teachers across T & uuml;rkiye and analyzed using confirmatory factor analysis and structural equation modeling. The results reveal that principal learning-centered leadership is directly and indirectly related to teacher collaboration via psychological safety. Our findings suggest that learning-centered leadership plays a pivotal role in cultivating teachers' collaborative practices by enhancing psychological safety. This study contributes to the existing knowledge base in school leadership, particularly within non-Western developing contexts, by highlighting the positive relationships between learning-centered leadership, psychological safety, and teacher collaboration.
Keywords: Member Exchange; School Leadership; Transformational Leadership; Task Conflict; Antecedents; Behavior; Trust; China; Voice